Juventude e protagonismo: contribuição do Projeto Beira da Linha para uma ação protagonista - Silva, Luciano Alves Farias da (2010)
The discussion about juvenile leadership in Brasil was expanded with more emphasis in the 90’s when it became part of the make work of various social movements, ONGs and academics study. The present studies bring the approach about youth an leadership focused on the contribuation made by the border line Project for the construction of educational actions. The work also bring an analysis of the actions of the Project with youth in the community of the district Alto do Mateus in João Pessoa. The period studied was the year 1991 to 2007 where used in qualitative research methodology, including some categories of studies such as: youth result shows of the existence of significant contribuation of PBL in the formation of the young protagonist in its social context, political and cultural.